Mitochondrial Ca2+ Handling in the Central Nervous System: the role of the mitochondrial Na+/Ca2+ exchanger (NCLX) in astrocyte metabolism and function - Costa, João Victor Cabral (2022)
Mitochondria are specialized organelles involved in many cellular processes, including redox balance, macromolecule biosynthesis, and energy metabolism. In the central nervous system, mitochondrial dysfunctions are associated with many pathophysiological mechanisms central toward neurological disorders such as stroke, Amyotrophic Lateral Sclerosis, and Alzheimer\'s, Parkinson\'s, and Huntington\'s diseases. One of the common hallmarks of these diseases lies in the mitochondrial Ca2+ handling system. Mitochondria have the ability to uptake and release Ca2+ through the mitochondrial calcium uniporter complex (MCUc) and Na+/Ca2+ exchanger (NCLX), respectively. This Ca2+ cycling, apart from shaping cytosolic Ca2+ levels, can modulate distinct mitochondrial metabolic pathways. In astrocytes, the most abundant macroglial cell type in the brain, Ca2+ signaling plays a central role controlling cellular homeostasis and function, influencing several brain processes such as synaptic plasticity, circuit integration, behavior, and neurodegeneration. However, apart from influencing cell proliferation and survival, little was known to date regarding the role of NCLX on astrocyte physiology. Searches in public RNA-seq databases led us to observe that astrocytes have overenriched Nclx transcription when in comparison to neurons or total brain areas, reinforcing our hypothesis that NCLX may present further critical physiological functions in this cell type. To study these functions, we inhibited NCLX activity - pharmacologically and genetically - in mouse primary culture astrocytes. In vitro NCLX inhibition increased cytosolic Ca2+ clearance and induced a metabolic shift, increasing glycolytic flux and lactate secretion. In vivo deletion of NCLX specifically in hippocampal astrocytes improved mouse performance in behavioral tasks, while cognitive impairment was induced by neuronal-specific NCLX deletion. These data reveal a novel role of NCLX as a modulator of glucose metabolism in astrocytes, with functional cognitive impacts